Brightspot Market sebagai Representasi Identitas “Cool” Kaum Muda di Jakarta - Junifer, Carolina (UI Scholars Hub, 2016)
Nowadays, the people still underestimate local fashion product. Moreover, many international brand’s stores seem to dominate the market. Then, Brightspot Market comes up with the curated market concept to accommodate and promote a premium quality of local fashion product. This Article discusses representation process to youth identity in Brightspot Market event. This article discusses the representation process of youth identity to enrich the study of cultural sociology, especially the concept of “circuit of culture” by Stuart Hall. This article describes Brightspot Market which modifies circuit of culture concept. Using qualitative methods by interview and observation towards Brightspot owners, local products’ vendor and consumer, this article shows that Brightspot Market can modify that concept by represents “the cool” identity through its curated market concept to Jakarta young people.